Niemann-Pick Disease Type C - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The neurologic symptomatology in 22 patients with Niemann-Pick disease type C have been analyzed and reported from the Developmental and Metabolic Neurology Branch, National Institute of Neurological Disorders and Stroke, National Institutes of Health, Bethesda, MD.